Union of Comoros : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Union of Comoros. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This 2016 Article IV Consultation highlights difficulties the economy of Comoros encountered in 2015 and the first half of 2016. An ongoing crisis in the electricity sector and slower-than-expected implementation of the public investment program were the main factors behind the slower growth. Inflation remained well anchored at an annual rate of about 2 percent. Fiscal policy was challenging for most of 2015 as the impact of slower economic growth was compounded by lower revenues. Growth is projected to pick up somewhat to 2 percent in 2016, and revenues are projected to increase to 12 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet